Simulation and modeling of the behavior in the four-stroke spark ignition engine by using CFD simulation - Abu Bakar, Muhammad Amirul Firdaus; Nadarajan, Arjunan; Khalid, Amir; Azizul, Muhamad Asri; Mohamed, Norirda; Mahmudin, Rahmah (Penerbit UTHM, 2020)
Computational fluid dynamics (CFD) is a branch of fluid mechanics that use numerical analysis and data structures to analyze and solves problems that involve fluid flows. CFD have been applied to a wide range of research and engineering problems in many fields of study and industries, including engine and combustion analysis. The objective of this review paper is to analyze the behavior in the four-stroke Spark Ignition (SI) engine by using CFD simulation. To get the require result a few methods have been used to analyze the behavior in the engine such as using CAD geometric model where the solid works software have been prepared. Then, in the CAD geometric model also have ANSYS software to perform analysis in engine module. To predict the behavior of the engine during its working two type of analysis can be performed namely port flow simulation and combustion simulation. So, in first part of this report, the CFD analysis is carried out to analyze the performance parameter, including intake stroke, compression stroke, power stroke and exhaust stroke with hexane fuel combustion. For the results, some details of the engine model and some predicted results including temperature, flow time and pressure profiles. With the existence of CFD simulation it can help many fields of study and industries by predict and analyze the possibility that can be happened in the future. At the same time, serves as a quick and economical way of future engine designs and concepts.